Cytokine profile of bronchoalveolar lavage in patients with and without checkpoint inhibitor pneumonitis - Michelle Ploch; Songzhu Zhao; Lai Wei; Joshua A. Englert; Sarah P. Cohen; Morgan A. Inks; Alexa S. Meara; Lynn A. Fussner; Dwight H. Owen; Kevin Ho (Cancer Immunology, Immunotherapy)
Abstract Background Checkpoint inhibitor pneumonitis (CIP) that develops following immune checkpoint inhibitor (ICI) treatment can be difficult to distinguish from other common etiologies of lung inflammation in cancer patients. Here, we evaluate the bronchoalveolar lavage fluid (BAL) for potential biomarkers specific to CIP. Methods We conducted a retrospective study of patients who underwent standard of care bronchoscopy to compare the cytokines of interest between patients with and without CIP and with and without immune-mediated pulmonary diseases. Pulmonary diagnoses were determined by the treating clinician at the time of bronchoscopy and retroactively reviewed for agreement by the study team. Results Thirty-seven patients were included, and 24 (64.9%) had pulmonary infection, 2 (5.4%) had pulmonary edema, 6 (16.2%) had non-CIP drug-induced pneumonitis, 3 (8.1%) had CIP, 5 (13.5%) had immune-mediated ILD or autoimmune vasculitis, 4 (10.8%) had cancer progression, and 4 (10.8%) had nonimmune-mediated interstitial lung disease (ILD). IL-6 from the BAL was significantly higher in patients with CIP compared to those with cancer progression and nonimmune-mediated ILD, and IL-6 was significantly higher in patients with immune-mediated pulmonary diseases compared to cancer progression, nonimmune-mediated ILD, and infection. Conclusions BAL IL-6 distinguished CIP from other common, important causes of pulmonary infiltrates in patients with cancer, suggesting it may give insight into the pathophysiology of CIP and has potential as a biomarker.